Alpha-defensin and the Synovasure lateral flow device for the diagnosis of prosthetic joint infection: a systematic review and meta-analysis. (June 2018) - Marson, B. A.; Deshmukh, S. R.; Grindlay, D. J. C.; Scammell, B. E.
Abstract : Aims: The aim of this review was to evaluate the available literature and to calculate the pooled sensitivity and specificity for the different alpha-defensin test systems that may be used to diagnose prosthetic joint infection (PJI). Materials and Methods: Studies using alpha-defensin or Synovasure (Zimmer Biomet, Warsaw, Indiana) to diagnose PJI were identified from systematic searches of electronic databases. The quality of the studies was evaluated using the Quality Assessment of Studies of Diagnostic Accuracy (QUADAS) tool. Meta-analysis was completed using a bivariate model. Results: A total of 11 eligible studies were included. The median QUADAS score was 13 (interquartile range 13 to 13) out of 14. Significant conflicts of interest were identified in five studies. The pooled sensitivity for the laboratory alpha-defensin test was 0.95 (95% confidence interval (CI) 0.91 to 0.98) and the pooled specificity was 0.97 (95% CI 0.95 to 0.98) for four studies with a threshold level of 5.2 mgl -1 The pooled sensitivity for the lateral flow cassette test was 0.85 (95% CI 0.74 to 0.92) and the pooled specificity was 0.90 (95% CI 0.91 to 0.98). There was a statistically significant difference in sensitivity (p = 0.019), but not specificity (p = 0.47). Conclusion: Laboratory-based alpha-defensin testing remains a promising tool for diagnosing PJI. The lateral flow cassette has a significantly lower performance and pooled results are comparable to the leucocyte esterase test. Further studies are required before the widespread adoption of the lateral flow cassette alpha-defensin test. Cite this article: Bone Joint J 2018;100-B:703–11.